Effectiveness of supply chain management with reference to apparel industry: a case study in India - Hishan, Sanil S. (Econjournals, 2016)
The study considered the apparel companies based in India to determine the supply chain management (SCM) techniques applied by these businesses as well as the benefits and difficulties encountered with its application thereby analyzing the effectiveness of the SCM in apparel industry. A questionnaire was used as a research instrument for this study to describe and assess the SCM systems of the selected apparel company executives. A well-structured questionnaire was distributed to the selected company executives involved in the supply chain activities. The questionnaire which evaluates seven different dimensions of SCM systems was given to the respondents and the effectiveness of the SCM practices of the apparel companies were measured in order to determine whether its systems are beneficial to the industry or not. Based on the findings it can be concluded that the apparel companies obtained a number of advantages out of SCM application with reference to the efficacy and responsiveness in delivering the goods or services to the customers. In spite of the beneficial effects of SCM application to the apparel industry, the companies are having certain difficulties with respect to the resistance to change and implementation of latest technologies. In spite of these difficulties with SCM, various alternatives are made available for them to enhance their systems like going for the third party logistics which help counter these problems. Considering that even expensive tools for SCM application have their downsides, difficulties in SCM is inevitable. However, companies using this can be resourceful in coming up with ways on how their systems can be improved.